AUDIT ENERGI UNTUK MENINGKATKAN EFISIENSI KONSUMSI ENERGI PADA JAKARTA DI GEDUNG - Prasetyo, Cahyono Heri; Zayadi, Ahmad (Bina Teknika, 2019)
Energy Audit to Improve Energy Consumption Efficiency in Building D Bank Indonesia, Electrical energy is one of the most important necessities of life for humans. Various human activities require electrical energy. Likewise, the activity in the D building which is one of the buildings in the Office Environment Bank Indonesia (KOPERBI) requires electrical energy is very large. Electrical energy is supplied from PLN 9,500 kVA connected power and back-up generator 5 x 1,500 kVA, equivalent to 7,500 kVA. Distribusui use electrical energy as follows: 8.56% lighting load, air conditioner (AC) 67.72% and 23.72% other building equipment. IKE standard used in Indonesia is the result of research conducted by ASEAN USAID in 1987 that a new report issued in 1992, which for the office's value is 240 kWh / m2 per year. IKE Building D BI is as follows IKE Initial Energy Audit is 250.03 kWh / m2.tahun, IKE Detailed Energy Audit is 239.81 kWh / m2.tahun, IKE Phase 1 After Implementation PHE is 224.02 kWh / m2 .tahun, IKE Phase 2 After Implementation PHE is 219.06 kWh / m2.tahun. Electrical energy consumption in Building the jakarta.